2010
DOI: 10.4067/s0717-95022010000200047
|View full text |Cite
|
Sign up to set email alerts
|

Viral Research in Brazilian Owls (Tyto alba and Rhinoptynx clamator) by Transmission Electron Microscopy

Abstract: SUMMARY:The barn-owl (Tyto Alba) and striped-owl (Rhinoptynx clamator) belong respectively to the families Tytonidae and Strigidae. Avian paramyxoviruses have been isolated from a variety of species of wild and domestic birds wordlwide causing diverse clinical symptoms and signs. Paramyxoviruses belong to the family Paramyxoviridae and Avulovirus genus, including nine serotypes (APMV 1 to 9). The lymphoid leukosis is a retrovirus-induced neoplasia. The avian retroviruses belong to the Retroviridae family and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
(58 reference statements)
2
3
0
Order By: Relevance
“…These results are in accordance with data in the literature showing particles with similar morphology in pigeons (Gough & Alexander, 1983), owls (Catroxo et al, 2010), ducks (Chang et al, 2001) and Gouldian Finch (Zhang et al, 2006).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results are in accordance with data in the literature showing particles with similar morphology in pigeons (Gough & Alexander, 1983), owls (Catroxo et al, 2010), ducks (Chang et al, 2001) and Gouldian Finch (Zhang et al, 2006).…”
Section: Discussionsupporting
confidence: 83%
“…The observation of typical particles of paramyxovirus and coronavirus in 3 (5.2%) out of 57 analyzed samples, corroborates with other authors who have found coronavirus in owls (Catroxo et al, 2010), quail (Circella et al, 2007) and green-cheeked (Gough et al, 2006).…”
Section: Discussionsupporting
confidence: 79%
“…Several authors using the same technique, described the presence of particles with morphological characteristics similar in other avian species, as budgerigar (Nerome et al), dove (Alexander et al, 1981;Catroxo et al, 2011), ringedteal (Gough & Alexander), parrot and parakeet (Steffens, 1998, Grund et al), yacinth macaw, rusty collared seedeater, red cowled cardinal, curl crested and peach fronted parakeet (Catroxo et al, 2000), duck (Chang et al, 2001), cockatiel (Clavijo et al), goose (Jinding et al, 2005), gouldian finch (Zhang et al), owl (Catroxo et al, 2010) and penguin (Miller et al; Fornells et al).…”
Section: Discussionmentioning
confidence: 99%
“…Pleomorphic rounded or elongated paramyxovirus particles, with a diameter of 100-500 nm, containing a envelope with a single fringe of surface projections approximately 17 nm in lenght, and helical herring-bone-like nucleocapsid, were visualized in the samples of organ fragments and feces of red-siskin (Spinus cucullata). In other avian paramyxovirus research, particles with these basic features were described by the negative staining technique in rusty collared seedeater and red cowled cardinal (Catroxo et al, 2000), Chloebia gouldiae (Zhang et al, 2006), owl (Catroxo et al, 2010), dove (Catroxo et al, 2011), helmeted manakin, common waxbill, double collared seedeater, rufousbellied thrush, great kiskadee, bananaquit, bay-winged cowbird, grey monjita, surucua trogon, green-winged saltator, common canary, wild canary, saffron finch, brazilian tanager, campo troupial, greatbilled, seedfinch, red-crested finch, ultramarine grosbeak, lined seedeater, variable oriole, seven colored tanager, hooded siskin, whitenaped jay, brassy breasted tanager, swallow tanager, buffy-fronted seedeater, gilt-edgerd tanager (Catroxo et al, 2012) and chestnutbellied seed-finch (Catroxo et al, 2022).…”
Section: Discussionmentioning
confidence: 99%